The Use of Cognitive Behavioral Therapy (CBT) to Reduce Obsessive Compulsive Disorder (OCD) Behavior - Maulida Fitri; Netrawati; Zadrian Ardi (Journal Of Psychology, Counseling And Education, 2024)
Obsessive Compulsive Disorder (OCD) includes recurring patterns of obsessions or compulsions, or a combination of both. Obsessions are persistent and intrusive thoughts that cause anxiety and are beyond the individual's ability to control. Compulsions are irresistible urges to perform certain behaviors repeatedly, such as bathing repeatedly, washing hands or clothes repeatedly. One of the counseling services provided for individuals with OCD is using the Cognitive Behavior Therapy (CBT) approach. The method used in this research is a literature study by collecting data from previous research results and relevant results. The objectives of the literature study in this research are 1) finding the problem to be researched, 2) looking for information and data that is relevant to the topic to be discussed, 3) adding new knowledge from the results of the research being studied, 4) testing the basic truth of the approach theory in the problem under study. Meanwhile, the analysis technique used is content analysis. The results of this research indicate that the CBT approach as a counseling service in alleviating the problems of individuals with OCD can be said to be effective. Several previous studies have used this approach in treating cases of individuals with OCD. This is because this approach can change the client's mindset or view of individuals with OCD from irrational in the form of repetitive behavior with obsessions and compulsions to rational. Apart from that, he is also able to express and develop the feelings he has, what he thinks and the behavior he carries out to be better than before.